2016
DOI: 10.5424/sjar/2016143-8347
|View full text |Cite
|
Sign up to set email alerts
|

Development of a remote sensing-based rice yield forecasting model

Abstract: This study aimed to develop a remote sensing-based method for forecasting rice yield by considering vegetation greenness conditions during initial and peak greenness stages of the crop; and implemented for “boro” rice in Bangladeshi context. In this research, we used Moderate Resolution Imaging Spectroradiometer (MODIS)-derived two 16-day composite of normalized difference vegetation index (NDVI) images at 250 m spatial resolution acquired during the initial (January 1 to January 16) and peak greenness (March … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 32 publications
2
18
0
1
Order By: Relevance
“…The results obtained through this improved CASA model, by addition of the constant likely to be useful for agronomists by providing more accurate estimates of NPP. rds: net primary production; biomass estimation; photosynthesis; respiration; rice ion period; net radiation uction ut three billion of the world's population consume rice (Oryza Sativa) as an essential p [1]. Almost 88% of global rice production is obtained from Asia [2].…”
Section: Ation Of Net Rice Production Through Improved a Model By Addmentioning
confidence: 99%
See 3 more Smart Citations
“…The results obtained through this improved CASA model, by addition of the constant likely to be useful for agronomists by providing more accurate estimates of NPP. rds: net primary production; biomass estimation; photosynthesis; respiration; rice ion period; net radiation uction ut three billion of the world's population consume rice (Oryza Sativa) as an essential p [1]. Almost 88% of global rice production is obtained from Asia [2].…”
Section: Ation Of Net Rice Production Through Improved a Model By Addmentioning
confidence: 99%
“…About three billion of the world's population consume rice (Oryza Sativa) as an essential food/crop [1]. Almost 88% of global rice production is obtained from Asia [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the field sizes are small and variable, and the use of high-resolution spatial images is preferable, to avoid mixed pixels. Unmanned aerial vehicles (UAVs), also called drones, have a distinct advantage at this point: UAV-based yield estimation has been investigated as a means of estimating field-level crop yield (Stroppiana et al, 2015;Mosleh et al, 2016;Teoh et al, 2016). These studies apply a regression model between a spectral index and the observed yield, for yield estimation purposes.…”
Section: Introductionmentioning
confidence: 99%